1985
DOI: 10.3168/jds.s0022-0302(85)80812-2
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Mechanisms of the Neonatal Intestine and Their Relationship to Immunoglobulin Absorption and Disease

Abstract: Immunoglobulin absorption by the calf has been the subject of considerable research. Despite these efforts little is known about the cytological events that occur at the level of the intestinal epithelial cell. These events have been studied extensively and characterized in the laboratory rodent; however, there have been few attempts to make corollaries between the two species. All neonatal animals display certain similarities in their intestinal morphology that may be correlated, with immunoglobulin absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0
7

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 54 publications
2
63
0
7
Order By: Relevance
“…All first colostrums used herein had bacterial loads slightly above this concentration, but transition milk was well below this figure (Table 1). It has been suggested that the presence of bacteria in the small intestine may impair IgG absorption (James and Polan, 1978;James et al, 1981;Staley and Bush, 1985). However, plasma IgG concentrations at birth and 6 h, 24 h, and 12 d relative to first colostrum intake were similar for all calves (Figure 1).…”
Section: Colostrum Quality and Igg Transfermentioning
confidence: 54%
See 1 more Smart Citation
“…All first colostrums used herein had bacterial loads slightly above this concentration, but transition milk was well below this figure (Table 1). It has been suggested that the presence of bacteria in the small intestine may impair IgG absorption (James and Polan, 1978;James et al, 1981;Staley and Bush, 1985). However, plasma IgG concentrations at birth and 6 h, 24 h, and 12 d relative to first colostrum intake were similar for all calves (Figure 1).…”
Section: Colostrum Quality and Igg Transfermentioning
confidence: 54%
“…Intestinal permeability can be transcellular (through epithelial cells by active or passive transport), which is mainly used for absorption of small molecules, or paracellular (through tight junctions that connect epithelial cells), which is mainly used for absorption of macromolecules (Bjarnason et al, 1995;Hall, 1999). Intestinal permeability is high in newborn calves during the first 24 to 36 h of life (Bush and Stanley, 1980;Besser and Gay, 1994), which is crucial to facilitate transfer of Ig from the colostrum into the calf bloodstream via a nonselective macromolecular transport system across the small intestinal epithelium (Staley and Bush, 1985). However, on the other hand, this increased permeability during the first few hours after birth renders the intestinal wall of newborn calves highly susceptible to bacterial translocation and increases the susceptibility to infections (Berg, 1995;Uil et al, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…The first day after birth is the most critical period for lambs, because either insufficient colostrum intake or a poor colostrum quality can lead to insufficient passive immunity (Ö ztabak and Ö zpinar, 2006;Rudovsky et al, 2008;Zarrilli et al, 2003). The ingestion of colostrum for passive immunity must be fast and complete since the intestinal absorption time of immunoglobulins lasts for up to 24 h (Nowak and Poindron, 2006;Zarrilli et al, 2003) and 36 h after birth (Devery et al, 1979), when closure of the intestinal lining and activation of an intracellural digestive system occurs (Staley and Bush, 1985). Several methods are available to detect failure of passive transfer in lambs.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7] During the first 24 hours after birth, a nonselective macromolecular transport mechanism in the small intestine of neonates transfers intact colostral immunoglobulins and other proteins from the intestinal lumen into the circulation. [8][9][10] Thereafter, closure of this absorption pathway occurs, which effectively terminates passive acquisition of humoral immunity. In addition to this nonselective mechanism for passive transfer of immunity, neonatal enterocytes possess a receptor-mediated mechanism specific for IgG transport.…”
mentioning
confidence: 99%